Do the elderly reduce housing equity? An international comparison - Maria Concetta Chiuri; Tullio Jappelli (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We explore the pattern of elderly homeownership using microeconomic surveys of 15 OECD countries, merging 60 national household surveys on about 300,000 individuals. In all countries the survey is repeated over time, permitting construction of an international dataset of repeated cross-sectional data. We find that ownership rates decline considerably after age 60 in all countries. However, a large part of the decline depends on cohort effects. Adjusting for them, we find that ownership rates start falling after age 70 and reach a percentage point per year decline after age 75. We find that differences across country ownership trajectories are correlated with indicators measuring the degree of market regulations.
urn:nbn:de:hebis:30-56931
Keywords: G2; R2; 330; Homeownership; Wealth Decumulation; Aging; Wohneigentum; Desinvestition; Alte Menschen; OECD-Staaten